Grass Snakes (Natrix natrix) as a Reservoir of Alaria alata and Other Parasites - Aneta Bełcik; Mirosław Różycki; Weronika Korpysa-Dzirba; Gianluca Marucci; Zbigniew Fafiński; Patrycja Fafińska; Jacek Karamon; Maciej Kochanowski; Tomasz Cencek; Ewa Bilska-Zając (Pathogens, 2022)
The aim of the study was to investigate the occurrence of Alaria alata (Goeze, 1782) in fifty-one grass snakes (Natrix natrix) collected in Gostynińsko-Włocławski Landscape Park. Each snake was tested for the presence of A. alata mesocercariae using the AMT and MSM methods. 18S ribosomal RNA (18S rRNA), cytochrome C oxidase subunit I (COI) and 28S ribosomal RNA (28S rRNA) genes were amplified by PCR and sequenced for the purpose of species identification. Fifty grass snakes were infected with helminths. The molecular characterization of trematodes allowed us to identify A. alata in 30 snakes (58.8%), Conodiplostomum spathula (Dubois, 1937) in 16 snakes (31.3%), Strigea falconis (Szidat, 1928) in 12 snakes (23.5%), and Neodiplostomum attenuatum (Linstow, 1906) in 2 snakes (3.9%), while, in 4 snakes (7.8%), the trematodes species could not be identified. Based on the analysis of 18S and COI sequences, Crenosoma vulpis (Dujardin, 1845) was identified in four snakes (7.8%), while nematodes collected from three snakes remained unidentified. The tapeworm sample was identified as Ophiotaenia. The obtained results indicate that grass snakes are an excellent vector of A. alata and may be a potential source of infection for mammals, e.g., wild boars and foxes, which results in an increased risk of alariosis for consumers of raw or undercooked game meat.